Effect of Yoga Vs Yang Tai-Chi on Balance and Quality of Life in Healthy Elderly: a Comparison - Atiya A Shaikh (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Objective To determine if Yoga intervention and tai chi intervention could improve balance and QOL in healthy elderly. To identify the most efficient balance training intervention amongst the two. Design A Pre-post design Setting Parks, Community centers Participants Total 83 healthy elderly (age range-65 yrs to 74 yrs) were recruited by chit method to either Yoga or Yang Tai-chi intervention group. 30 participants in each group completed the intervention program. Intervention A 6-week Yoga or Yang Tai Chi intervention specifically tailored to elderly and designed to improve strength, flexibility and proprioception was performed by healthy elderly. Participants attended five 40-minute exercise classes per week. Main Outcome Measures Forward reach test (FRT), Timed Up and Go test (TUG), Berg Balance Scale (BBS), Quality of life Questionnaire (SF-36) Results There was a significant difference in scores before and after 6 weeks of intervention (P<0.0001).Yang Tai chi exercise intervention showed a more significant difference in all outcome measures before and at end of intervention program as compared to Yoga intervention(P=0.049,0.0002,0.0004,<0.0001 for FRT,TUG,BBS,SF-36 respectively). Conclusion Both exercise interventions improve balance and QOL in healthy elderly. Yang Tai Chi intervention was more effective to improve balance and QOL as compared to Yoga intervention.